The Regional Western Sweden SOM Survey 1992 - SOM Institute, University of Gothenburg (University of Gothenburg, 1994)
Since 1986 an annual nationwide survey, called SOM-survey, has been carried out at Göteborg University. In 1992 a similar survey was carried out in Western Sweden, i.e. Göteborg and eleven neighbour municipalities. The purpose of this survey was to shed light on opinions in Western Sweden and their development over time, and also to study how they relate to opinions in Sweden as a whole. The questionnaire was divided into five subject fields: mass media; politics and society; the municipality of Göteborg; energy, nuclear power and environment; and background. This questionnaire is partly a replication of the one used in the nationwide SOM-survey, but there is also a number of questions dealing with the situation in Göteborg and neighbouring municipalities. The questions about mass media dealt with how often the respondents read a number of daily papers; how often they listen to different radio channels; the trustworthiness of the reports of local events in a number of media; time spent daily viewing television, reading morning paper and reading evening paper; how often the respondent watch a number of news programs in television; how often the respondent watch different television channels; subscription of morning paper; and importance of a number of news paper contents. In the politics and society section you could find questions about the respondent´s interest in politics in general and in local politics; opinion on the most important local issues; opinion on a number of proposals occurring in the political debate and on the way the local government handles their duties; opinion on a Swedish EC-membership; political party preferred; confidence in different groupings in society; services used by the respondent or close relative, and if the respondent´s occupation was within any of these service sectors; opinion on the local service and areas to increase/decrease; preferences when it comes to lowering local taxes or extend local authority service; opinion on the local government administration and its employees with regard to the respondents´ own experiences; efforts to influence a local government decision; most suited to handle a number of local services; financing of a number of activities; misuse of social assistance and services; opinion on the local government finances; organisational solution of the regional cooperation in Western Sweden. Respondents living in Göteborg had to answer a number of questions about neighbourhood committees. Questions concerning energy and nuclear power dealt with the respondent´s attitude toward nuclear power and how they experienced different risks in connection with the use of nuclear power. The respondents also had to indicate how threatening they considered a number of environmental problems. Social background included questions on housing, occupation, union membership, education, marital status, size of household, income, equipment in household and household´s yearly expense for a number of items, and voting intention at a hypothetical election the same day.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Sedan 1986 har projektet Samhälle Opinion Massmedia (SOM) genomfört årliga rikstäckande undersökningar av svensk opinion. Hösten 1992 kompletterades den nationella undersökningen med en västsvensk undersökning vars syfte är att följa opinionsutvecklingen i Västsverige och kunna jämföra med åsiktsmönstren i hela landet. Väst-SOMs frågeformulär indelades i fem ämnesområden: massmedia; politik och samhälle; Göteborgs kommun; energi, kärnkraft och miljö; samt bakgrundsfrågor. Frågeformuläret var huvudsakligen en replikation av det som användes i den nationella SOM-undersökningen, men där fanns också ett antal frågor som tog upp situationen i Göteborg och dess kranskommuner. Frågor om massmedier behandlade hur ofta man läser ett antal dagstidningar; hur ofta man lyssnar på olika radiokanaler; hur tillförlitliga man bedömer olika medier vara då det gäller bevakningen av vad som händer i kommunen; genomsnittlig tid ägnad dagligen åt TV-tittande samt morgontidnings- respektive kvällstidningsläsande; tittande på olika typer av nyhetsprogram i TV; tittande på olika TV-kanaler; prenumeration på morgontidning; och hur viktiga man anser olika typer av tidningsinnehåll vara. I avsnittet politik och samhälle återfinns frågor om politiskt intresse i allmänhet samt intresse för lokalpolitik; åsikt om vilka kommunala frågor som är viktigast; inställning till ett antal förslag som förekommit i den politiska debatten och om hur kommunstyrelsen sköter sin uppgift, inställning till ett svenskt EG-medlemskap; bästa politiska parti; förtroende för olika grupper i samhället; service utnyttjad av respondenten eller nära anhörig samt om respondenten arbetar inom något av dessa serviceområden; inställning till den kommunala servicen och till vem som är bäst lämpad att sköta olika typer av service; organisatorisk lösning av det regionala samarbetet i Västsverige; samt kunskap om och inställning till stadsdelsnämnderna i Göteborg. Frågorna om energi, kärnkraft och miljö tog upp respondentens inställning till kärnkraften och hur man upplever olika risker i samband med kärnkraften. Dessutom fick man ange hur allvarliga hot man ansåg ett antal miljöproblem vara mot miljön. Bakgrundsfrågorna inkluderar uppgifter om bostad, sysselsättning, fackföreningstillhörighet, utbildning, civilstånd, hushållets storlek, inkomst, utrustning i hushållet samt hur man skulle ha röstat om det var val samma dag undersökningen ägde rum.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1992
Väst-SOM 1992
Keywords: housing; boende; mass media; massmedia; public sector; offentlig sektor; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; news; nyheter; internal politics; inrikespolitik; political parties; politiska partier; housing conditions; bostadsförhållande; european economic community; europeiska ekonomiska gemenskapen; leisure time activities; fritidsaktiviteter; social activities (leisure); sociala aktiviteter (fritid); energy supply; energiförsörjning; political party policies; politiska partiers politik; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap